Factors Influencing the Degree of Disability in Patients With Multiple Sclerosis - Xue, Huiru; Yang, Zhenzhen; Wang, Li; Jiang, Yayun; Li, Jiayang; Wu, Minghui; Wang, Guilian; Zhang, Yuanyuan; Zhang, Meini (Frontiers in Neurology, 2021)
Objective: To explore the factors influencing the degree of disability in patients with multiple sclerosis (MS), and to provide evidence for its early diagnosis, prognostic evaluation and clinical intervention. Methods: This retrospective observational study included 72 patients with relapsing-remitting multiple sclerosis (RRMS) at the First Hospital of Shanxi Medical University. All patients completed craniocerebral and spinal cord MRI (with or without Gd enhancement) and were evaluated for Expanded Disability Status Score (EDSS) scores before receiving treatment. Results: Among 72 patients with RRMS, 45 (62.5%) had an EDSS score ≤3; A total of 27 patients (37.5%) had an EDSS score >3 points. Univariate analysis showed that age, annual recurrence rate (ARR), drug use, albumin (ALB), triglycerides (TG), and total number of lesions in groups with EDSS score ≤ 3 were significantly different from those with an EDSS score > 3 points (P<0.05). Multivariate logistic regression analysis showed that ALB, total number of lesions, and drug use were independent influencing factors of the degree of disability in patients with MS, and the difference was statistically significant (P<0.05). An ROC curve was constructed using ALB and the total number of lesions. The AUC of ALB was 0.681, P <0.05, and the best cut-off value was 44.2 g/L. Its sensitivity to predict the degree of disability in patients with multiple sclerosis was 85.2%, while its specificity was 51.1%. The AUC of the total number of lesions was 0.665 ( P<0.05) and the best cut-off value was 5.5. Its sensitivity to predict the degree of disability in patients with multiple sclerosis was 70.4%, while its specificity was 64.4%. The AUC of the combined ALB, total number of lesions, and drug use was 0.795 ( P<0.05), sensitivity was 77.8, and specificity was 73.3%. The optimal diagnostic cut-off value of the regression equation for the EDSS score of patients with multiple sclerosis was 0.420. Conclusion: Serum ALB, total number of lesions, and drug use in patients with multiple sclerosis were independent factors influencing the degree of disability. These findings provide clinical evidence for the prognostic evaluation and early intervention of patients with multiple sclerosis.